Applying Next-Generation Sequencing Platforms for Pharmacogenomic Testing in Clinical Practice - Tafazoli, Alireza; Guchelaar, Henk-Jan; Miltyk, Wojciech; Kretowski, Adam J.; Swen, Jesse J. (Frontiers in Pharmacology, 2021)
Pharmacogenomics (PGx) studies the use of genetic data to optimize drug therapy. Numerous clinical centers have commenced implementing pharmacogenetic tests in clinical routines. Next-Generation Sequencing (NGS) technologies are emerging as a more comprehensive and time and cost-effective approach in PGx. This review presents main considerations for applying NGS in guiding drug treatment in clinical practice. It discusses both advantages and challenges of implementing NGS-based tests in PGx. Moreover, limitations of each NGS platform are revealed, and solutions for set up and management of these technologies in clinical practice are addressed.